2012
DOI: 10.1159/000332084
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Biomarkers and Noninvasive Predictors of Atherosclerosis in Chronic Peritoneal Dialysis Patients

Abstract: Background: We investigated the relationship among serum cardiac biomarkers including N-terminal pro-brain natriuretic peptide (NT-pro-BNP), cardiac troponin T (cTnT), uric acid and high-sensitive C-reactive protein (hs-CRP) and noninvasive predictors of atherosclerosis including carotid intima-media thickness (IMT), aortic stiffness (pulse wave velocity (PWV)) and transthoracic coronary flow reserve (CFR) in peritoneal dialysis (PD) patients. Methods: 37 PD patients were included in the study. We measured (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 77 publications
2
18
0
2
Order By: Relevance
“…The measurement of CCA IMT using high-resolution ultrasonography has been suggested as an excellent marker of subclinical atherosclerosis. However, there are few studies about CCA IMT and atherosclerosis indicating that the CCA diameter represents an indirect indicator of the stiffness of the arterial wall [25]. In our study, female gender, body mass index, C-reactive protein and ET-1 were determined as independent predictors of an increased CCA IMT, whereas serum albumin, hemoglobin, low-density lipoprotein and age were identified as predictors of rigidity of the arterial wall.…”
Section: Discussionmentioning
confidence: 51%
“…The measurement of CCA IMT using high-resolution ultrasonography has been suggested as an excellent marker of subclinical atherosclerosis. However, there are few studies about CCA IMT and atherosclerosis indicating that the CCA diameter represents an indirect indicator of the stiffness of the arterial wall [25]. In our study, female gender, body mass index, C-reactive protein and ET-1 were determined as independent predictors of an increased CCA IMT, whereas serum albumin, hemoglobin, low-density lipoprotein and age were identified as predictors of rigidity of the arterial wall.…”
Section: Discussionmentioning
confidence: 51%
“…Experimental models have shown that hypoxic myocardial tissue results in the production of extra BNP, suggesting that BNP could potentially serve as a biomarker of myocardial ischemia. [13][14][15]28,33 These experimental data were confirmed in a number of small-scale clinical studies, which were summarized in a meta-analysis. [13][14][15] These data indicate that Figure 1.…”
Section: Discussionmentioning
confidence: 66%
“…Although cTnT elevation is assumed to be the result of clinically silent myocardial ischemia and micro-infarctions, cTnT also has been found to be elevated in patients with heart failure in the absence of acute ischemia and in CKD patients with LVH without myocardial necrosis. 13,14 Furthermore, studies evaluating the relation between cTnT and left ventricular parameters have shown contrasting results. Mallamaci and others [34][35][36] suggested that cTnT had a significant correlation with LVH and left ventricular systolic dysfunction in 258 HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CANUSA study demonstrated that survival in patients on PD was affected by the presence of RRF (21) . Caliskan et al (22) in their study on PD patients reported that the risk of development of AS increased with a decreased RRF. Huang et al (23) showed an independent inverse correlation between RRF and AS determined by baPWV.…”
Section: Discussionmentioning
confidence: 95%